Short self‐assembling cationic antimicrobial peptide mimetics based on a 3, 5‐diaminobenzoic acid scaffold. Issue 1 (17th July 2019) - Thota, Chaitanya K.; Berger, Allison A.; Harms, Björn; Seidel, Maria; Böttcher, Christoph; von Berlepsch, Hans; Xie, Chaunxiong; Süssmuth, Roderich; Roth, Christian; Koksch, Beate
Abstract: Infections caused by Staphylococcal and Micrococcal species represent a major public health burden. Although treatments do exist, these tend to be associated with cytotoxic effects; furthermore, the emergence of antimicrobial resistance presents an immediate challenge. New classes of active compounds are required to address these threats to human health. Here we present a de novo peptidomimetic strategy that produces self‐assembling cationic antimicrobials. To identify a candidate compound with bactericidal activity, a small library of 8 peptidomimetics comprising ultrashort peptide sequences attached to a 3, 5‐diaminobenzoic acid scaffold was generated and tested against Micrococcus luteus and Staphylococcus aureus . Self‐assembly appears to be the driving force for increased potency, likely by contributing to increased local surface charge density and peptide mass and producing a multivalent effect that enhances electrostatic interactions with negatively charged bacterial membranes, causing membrane disruption. The most active library member C7 forms patched micellar nanoparticles and has an activity higher than that of known natural antimicrobial peptides against M luteus . C7 also shows activity comparable to that of gramicidin S and the standard antibiotic vancomycin used in antibacterial therapy, but with a greater selectivity index. Importantly, C7 is also nontoxic and nonhemolytic, unlike the currently administered vancomycin, which can cause acute renal failure, and gramicidin S, which is highly hemolytic in nature. The short sequence length, ease of design, convenient synthesis strategy, and presence of a substitutable hydrophobic residue that enables self‐assembly into different nanostructures make this model compound highly attractive for generating cost‐effective, rapid‐acting peptide‐based antimicrobials. Abstract :